2016
DOI: 10.1038/srep37509
|View full text |Cite
|
Sign up to set email alerts
|

miR-706 inhibits the oxidative stress-induced activation of PKCα/TAOK1 in liver fibrogenesis

Abstract: Oxidative stress induces the activation of liver fibrogenic cells (myofibroblasts), thus promoting the expression of fibrosis-related genes, leading to hepatic fibrogenesis. MicroRNAs (miRNAs) are a new class of small RNAs ~18–25 nucleotides in length involved in post-transcriptional regulation of gene expression. Wound-healing and remodeling processes in liver fibrosis have been associated with changes in hepatic miRNA expression. However, the role of miR-706 in liver fibrogenesis is currently unknown. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Oxidative stress was found to induce α-SMA (α-smooth muscle actin), PKCα (Protein kinase Cα), and TAOK1 expression during liver fibrogenesis. MicroRNA miR-706 directly inhibits PKCα and TAOK1 expression via binding to their 3′-untranslated regions, thus preventing the epithelial to mesenchymal transition and alleviating hepatic fibrosis [ 68 ]. Jing et al [ 69 ] showed that miR-381-3p promoted chondrogenesis in umbilical cord mesenchymal stem cells through direct suppression of TAOK1 and the downstream Hippo signaling pathway, indicating that TAOK1 may regulate chondrogenesis via the Hippo cascade.…”
Section: Tao Kinases In Other Physiological Processes and Diseasesmentioning
confidence: 99%
“…Oxidative stress was found to induce α-SMA (α-smooth muscle actin), PKCα (Protein kinase Cα), and TAOK1 expression during liver fibrogenesis. MicroRNA miR-706 directly inhibits PKCα and TAOK1 expression via binding to their 3′-untranslated regions, thus preventing the epithelial to mesenchymal transition and alleviating hepatic fibrosis [ 68 ]. Jing et al [ 69 ] showed that miR-381-3p promoted chondrogenesis in umbilical cord mesenchymal stem cells through direct suppression of TAOK1 and the downstream Hippo signaling pathway, indicating that TAOK1 may regulate chondrogenesis via the Hippo cascade.…”
Section: Tao Kinases In Other Physiological Processes and Diseasesmentioning
confidence: 99%
“…It has been reported that OS can activate the liver fibrogenic cells (myofibroblasts) to upregulate fibrosis-related genes, leading to hepatic fibrogenesis. MiR-706, a liver-enriched miRNA, has been found to inhibit OS-induced hepatic fibrogenesis by directly targeting PKC α and TAOK1 [132]. Hepatic miR-192-5p has been found to be significantly downregulated in OS-induced acute liver injury, being dependent on stimulation with TNF.…”
Section: Stress and Mirnasmentioning
confidence: 99%
“…In A. Fumigatus-exposed mice, mir-706 expression was increased (28); however, after strain A exposure, miR-706 consistently had the highest fold change for all time points, except 24 hours after 13 weeks, when miR-21a-5p expression was highest (Table 6). miR-706 is involved in liver fibrogenesis (46); however, the present results also suggest involvement in pulmonary tissue remodeling. In agreement with the present study, miR-21a is involved in pulmonary fibrogenesis (47) and was surprisingly decreased after A. fumigatus exposure (28).…”
Section: Discussionmentioning
confidence: 44%